BUILD FAMILY COMMUNICATION DURING THE COVID-19 PANDEMIC - Dewi Widowati; Ari Widodo; Yackie (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
The COVID-19 pandemic, which has been running for more than two years, has changed people's lives and routines, affecting all fields, be it economics, politics, social, culture and education. Teaching and learning activities are also carried out at home. Children are more often at home than outside. Therefore, parents need to build communication within the family through intense interaction with their children. This study discusses how the efforts made by parents during the covid pandemic. The Interaction and Transactional Theory used in this study discusses how a relationship is built from just an interaction but also goes to the transactional side. The method used is descriptive qualitative to describe the atmosphere in the family when parents try to build communication with children intensely, namely by interacting through communication, both verbal and nonverbal. The data collection technique was by conducting interviews each via e-mail and whatsapp on several families (informants) who have children aged 4-15 years. The findings show that during the COVID-19 pandemic, parents communicated by directing their children to study between the morning and evening hours. According to them, it is quite difficult to direct children to study, because they prefer to watch television or video/games, and play with their favorite toys. Children need to be persuaded to stay willing to learn or do positive activities so they don't get bored. But in the end the children are also willing to learn and do positive activities after parents communicate well about the importance of learning.